Fertility, Non-Altruism and Economic Growth: Industrialization in the Nineteenth Century - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2002)
This paper presents a model of fertility, which is specific for the industrialization that took place during the nineteenth century and which was concurrent with the demographic transition that occurred over the period. While previous research on demographic transition assumed altruism as the main element explaining the increase in fertility rates, this paper does not, since altruism seems irrelevant over this period. The relationship between parents and children is part of a whole set of values and social norms that evolved over time and were affected by changes in the economic environment. In the nineteenth century, parental behavior was not compatible with altruism. I therefore present a model that suits the social norms of the nineteenth century. The value that seems to correspond to the legal system and social norms regarding the parent-child relationship of the period of industrialization is perpetuation. Due to a budget constraint on workers, perpetuation is displayed differently in different social classes. This paper will therefore focus on the interaction between the different social classes and show how industrialization is linked to demographic transition.
Keywords: J13; O11; O16; O40; 330; altruism; social classes; demographic transition; capital; proletariat; fertility; growth